Enhancing antibody patent protection using epitope mapping information - Deng, Xiaoxiang (MAbs, 2017)
As the $100B therapeutic monoclonal antibody (mAb) market continues to grow, developers of therapeutic mAbs increasingly face the need to strengthen patent protection of their products and enforce their patents in courts. In view of changes in the patent law landscape, patent applications are strategically using information on the precise binding sites of their mAbs, i.e., the epitopes, to support patent novelty, non-obviousness, subject matter, and a tightened written description requirement for broad genus antibody claims. Epitope data can also allow freedom-to-operate for second-generation mAbs by differentiation from patented first-generation mAbs. Numerous high profile court cases, including Amgen v. Sanofi over rival mAbs that block PCSK9 activity, have been centered on epitope mapping claims, highlighting the importance of epitopes in determining broad mAb patent rights. Based on these cases, epitope mapping claims must describe a sufficiently large number of mAbs that share an epitope, and each epitope must be described at amino acid resolution. Here, we review current best practices for the use of epitope information to overcome the increasing challenges of patenting mAbs, and how the quality, conformation, and resolution of epitope residue data can influence the breadth and strength of mAb patents.